Effects of Chest Physiotherapy and Effective Cough Exercise on Sputum Clearance and Respiratory Frequency in Tuberculosis Patients - Yoga Handita Windiastoni; Nur Basuki; Nurul Fithriati Haritsah (Masters Program in Public Health, 2023)
Background: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. Chest physiotherapy and cough exercises are one of the commonly used methods as part of TB treatment. This study aimed to determine the effects of chest physiotherapy and cough exercises on sputum clearance and respiratory frequency in TB patients. Subjects and Method: This was a quasy experiment study with no control group. The study was conducted at Dungus Respiratory Hospital, Madiun, East Java. A sample of 26 TB patients was selected purposively. The independent variables in the study were effective cough and chest physiotherapy. The dependent variable in this study was sputum discharge. Chest and cough physiotherapy interventions are effective in patients 3 times. This study used a measuring instrument in the form of a sputum glass. The data collected were analyzed quantitatively using the Mann-Whitney test to determine the effect of chest physiotherapy and effective cough exercises on pulmonary tuberculosis conditions. Results: After combination interventions of chest physiotherapy and effective cough exercises, sputum released (Mean= 29.35; SD= 0.85) was higher than before (Mean= 23.65; SD= 0.68). Respiratory frequency after intervention (Mean= 25.88; SD= 0.73) was higher than before (Mean= 27.12; SD= 0.98). Conclusion: Sputum secretion and respiratory frequency are higher than before chest physiotherapy and cough exercises in TB patients. Keywords: chest physiotherapy, cough exercise, physiotherapy, tuberculosis. Correspondence:Nurul Fithriati Haristah. Study Program of Physiotherapy, Health Polytechnics, Ministry of Health Surakarta. Email: nurulfithriati_haritsa@yahoo.com. Mobile: +6285157577816.